Teacher-led design of an adaptive learning environment - Mavroudi, Anna; Hadzilacos, Thanasis; Kalles, Dimitris; Gregoriades, Andreas (My University, 2016)
This paper discusses a requirements engineering process that exemplifies teacher-led design in the case of an envisioned system for adaptive learning. Such a design poses various challenges and still remains an open research issue in the field of adaptive learning. Starting from a scenario-based elicitation method, the whole process was highly participatory, with requirements validation in iterative cycles. The contribution of the paper is twofold: (a) it exposes the design of an environment which addresses the related challenges mentioned by the participants and the literature and (b) it suggests a methodology of framing key requirements into a set of critical success factors for meeting the end-users’ expectations. The latter could be crucial in cases where the available resources are limited, but the quality of the product must not be sacrificed.
Keywords: adaptive learning; learning Design; requirements engineering; teachers as designers; user-centred design